أثر الدراسات الثقافیة الغربیة في النقد العربي المعاصر: دراسة تحليلية تأصيلية - سايحى، جمال; بودربالة، الطيب Bouderbalah, Altayeb (جامعة باتنه 1 - كلية العلوم الإسلامية, 2019)
تهدف هذه الدراسة إلى تتبع المنابع الأصلية التي انبثقت منها الدراسات الثقافية المعاصرة، سواء أكان ذلك في العالم الغربي أم في العالم العربي، على اعتبار أن الدراسات الثقافية المعاصرة شكلت نقطة حاسمة في تحول الدراسات النقدية التي رافقت الحداثة وما بعد الحداثة، وعلى هذا فإن الدارسين للنقد الأدبي نقلوا اهتمامهم من الأجناس الأدبية التقليدية؛ كالقصيدة العمودية والقصيدة الحرة والسرديات...، إلى الاشتغال بالدراسات النقدية الثقافية. وتمثل وسائل الإعلام والتواصل الحديثة الركيزة الأساسية في إحداث هذا التحول، ذلك أنها نقلت الفكر الإنساني من ثقافة المشافهة والكتابة إلى ثقافة الصورة البصرية، ومن ثم فإن الدراسة تقوم بتسليط الضوء على هذه المحاور المفصلية في تحولات الدراسات النقدية المعاصرة. كما تهدف الدراسة أيضا إلى تقديم مقاربة نقدية للمحاولات العربية التي قام روادها بطرح أفكار ثم بلورتها لتبلغ إلى نظرية نقدية معاصرة، وستتخذ الدراسة المنهج الوصفي التحليلي وسيلة لبلوغ الأهداف المسطرة لها. وانطلاقا من هذا التقديم فإن الدراسة تطرح التساؤلات الآتية: - ما المقصود بالدراسات النقدية الثقافية؟ وما هي العلاقة بينها وبين النقد الأدبي؟ وما هو الدور الذي قامت به وسائل التواصل الحديثة في هذا المجال؟ - وهل بإمكان الدراسات النقدية الثقافية أن تحل مكان النظريات النقدية في البلاغة العربية وتصير بديلا نهائيا عنها؟
This study aims to track the original sources from which contemporary cultural studies have emerged, whether it is in the Western world or in the Arab world, as contemporary cultural studies have formed a critical point in the transformation of the critical studies that accompanied modernity and postmodernity, and thus the scholars of criticism Literary have shifted their interest from traditional literary races, such as the vertical poem, free poem, narratives ... to engaging in cultural critical studies. The media and modern communication are the main pillar in bringing about this transformation, as they moved human thought from the culture of writing and writing to the culture of the visual image, and then the study sheds light on these articulated axes in the transformations of contemporary critical studies. The study also aims to provide a critical approach to the Arab attempts that its leaders put forth ideas and then crystallized them to reach a contemporary critical theory, and the study will take the descriptive analytical method as a way to achieve the objectives outlined to it. Based on this introduction, the study raises the following questions: What is meant by cultural critical studies? What is the relationship between it and literary criticism? What is the role played by modern means of communication in this field? Can cultural critical studies replace the critical theories in Arabic rhetoric and become a final alternative to them?
Keywords: النقد العربى -- الدراسات الغربية -- النقد الادبى